Anaerobic reactor applied to laundry wastewater treatment: Unveiling the microbial community by gene and genome-centric approaches. (April 2020) - Delforno, T.P.; Belgini, Daiane R.B.; Hidalgo, K.J.; Centurion, Victor B.; Lacerda-Júnior, G.V.; Duarte, Iolanda C.S.; Varesche, M.B.A.; Oliveira, V.M.
Abstract: Gene and genome-centric approaches were applied to investigate the microbial taxonomic and metabolic diversity profiles from a lab-scale anaerobic reactor applied to laundry wastewater treatment with increasing concentrations of linear alkylbenzene sulfonate (LAS). Therefore, metagenomic analysis was carried out with reactor samples collected under three conditions, (i) Stage I, the reactor was fed with synthetic medium, (ii) Stage II, synthetic medium was replaced by diluted laundry wastewater with specific LAS loading rates (SLLRs) of 1.0 ± 0.3 mgLASgTVS −1 d −1 and (iii) Stage III, SLLRs increased to 2.7 ± 0.7 mgLASgTVS −1 d −1 . Shotgun metagenomic sequencing was performed on an Illumina HiSeq 2 × 150 bp platform. Gene-centric analysis of each step of the metabolic pathway (fumarate addition, β-oxidation, ring cleavage and desulfonation) for anaerobic aromatic degradation showed eight over-representative genera (Achromobacter, Pelodictyon, Pseudomonas, Psychrobacter, Rhodococcus, Stenotrophomonas, Sulfurovum and Syntrophobacter), suggesting a microbial core with an important role in LAS biodegradation. Some of these genera were also recovered through a differential binning method, representing fifteen bacterial and one archaeal metagenome-assembled genomes (MAGs). Biodegradation pathway reconstruction of LAS using six MAGs unveiled the syntrophism for complete degradation of the LAS molecule. Only the MAGs with taxonomic annotation for Syntrophobacter showed genetic potential for fumarate addition, whereas in the ring cleavage, there was a predominance of genes in MAGs with taxonomic annotation for Pseudomonas fragi and Rhodococcus. This work represents the first report of genome-centric approach to study biological reactors applied in anionic surfactant degradation, contributing with detailed metabolic information of the key microbial actors in LAS degradation and opening perspectives for future biotechnological strategies aiming at bioaugmentation and/or biostimulation of indigenous microbial populations. Graphical abstract: Image 1 Highlights: Lab-scale reactor was applied to laundry wastewater treatment. Gene and genome-centric approaches were applied to investigate the microbiome. Eight over-representative genera were related with surfactant degradation. Six out of 16 MAGs showed a strong genetic potential for LAS biodegradation. Biodegradation pathway reconstruction of Linear Alkylbenzene Sulfonate using MAGs.